KOMPETENSI ALUMNI EKONOMI SYARIAH DALAM PERANNYA PENINGKATAN SUMBERDAYA MANUSIA PADA INDUSTRI HALAL - Muhammad Aswad (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2023)
The number of graduates on Islamic economics degree whose careers in the halal industri sector are limited due to low number of graduates who are certified in HR management in companies. This is of an objective conditions faced by graduates who hold Islamic Economics today. This indicates that there is a gap in terms of number of graduates who are able to be absorbed by the halal industri sector and Islamic financial institutions where only 9.1% are in accordance with their university educational background. There is a disparity in the competence and qualifications of human resources since the graduates are not equipped with adequate technical competence as required by the industri. This study used Interpretative Structure Modelling (ISM) method to examine efforts in structuring the complex needs, goals, actors and competence constraints of graduates from a model system. The results of this study revealed that the key elements of competency requirements are (1) the need for Islamic economics graduates to have hard skill and soft skill competencies. (2) the actors of competency development are Higher Education Institutions (3) The goal of competence is to create skilled human resources, (4) the obstacle in developing competence is the incompatibility of the higher education curriculum with industri needs.